Farming challenges in North Alego, Kenya - Braslow, Juliet; Okolo, Wendy (2016)
This participatory video was filmed, produced, and directed by members of the Rafiki Farmers Group in North Alego, Kenya. With this video they want to communicate the message: knowledge and training on farming practices and markets can help them address some of the challenges they face. Through a 6 day process facilitated by Juliet Braslow (CIAT) and Wendy Okolo (CIAT), the farmers learned video techniques, interviewing skills, and developed the story they wanted to share with their community, local leaders, and the world. A shortened version can be found here - https://youtu.be/QTUUP6RYWSQ.